Preliminary investigation on performance of photodiode sensor as a dosimeter - Y. Md Radzi; N. Zulkafli; A. Omar (Biomedical Photonics)
Radiation dosimetry in the health and medicine field is crucial to ensure there is no unnecessary ionizing radiation exposure to patients and personnel. While various types of semiconductor dosimeters are available, photodiode sensors are seen as a reliable and cost-effective immediate dosimeter. This study investigates the capabilities of a monolithic photodiode with an on-chip trans-impedance amplifier as a dosimeter in diagnostic radiology. A photodiode sensor covered with black insulation tape is irradiated with the diagnostic x-ray of potential in range between 40 to 90 kV with constant tube current-time product of 50 mAs at 60 cm source-to-detector distance (SDD). Exposures of different tube current at the range of 10 to 250 mA with a constant tube voltage of 70 kVp at the same setup are made. The photodiode sensor connected to the electrometer gives out readings in the millivolt (mV), and the output of the photodiode and semiconductor detector is recorded. The photodiode’s energy dependency, reproducibility, dose response, and distance dependency were evaluated as the capabilities of the photodiode to be used as a dosimeter. For energy dependency, it shows a linearity of 0.9458, while the response to increasing tube current with a constant tube voltage shows the R2 of 0.912. The photodiode shows good dependency on the tube voltage and tube current. Other than that, it also showed a linear coefficient of 0.5138 for distance dependence which is considered as a good linearity fit value for a photodiode as initial performance. However, its reproducibility is poor due to its large capacitance. This monolithic photodiode with an on-chip trans-impedance amplifier has demonstrated good results for energy dependency but poor results for reproducibility. However, the photodiode can be improvised in the future to ensure it is suitable as a dosimeter.